Risk Factors Associated with NSAID-Induced Upper Gastrointestinal Bleeding Resulting in Hospital Admissions: A Cross-Sectional, Retrospective, Case Series Analysis in Valencia, Spain (2007)
ABSTRACT: Background: NSAIDs are a significant cause of drug-related hospital ad missions and deaths. The therapeutic effects of NSAIDs have been associated with the risk for developing adverse events, mainly in the gastrointestinal tract. Objectives: The focus of this study was to identify the most common risk factors associated with NSAID-induced upper gastrointestinal bleeding (UGIB) resulting in hospital admissions. A secondary end point was the relationship between use of gastroprotective treatment and relevant risk factors to NSAID induced UGIB in the selected population. Methods: This study was a cross-sectional, retrospective, case-series analy sis of NSAID-induced UGIB resulting in hospital admission to the Requena General Hospital, Valencia, Spain, occurring from 1997 to 2005. International Classification of Diseases, Ninth Revision, Clinical Modification codes were used to identify UGIB admissions associated with NSAIDs. To estimate the probabil ity of association between UGIB and the use of NSAIDs, the Naranjo adverse drug reaction probability was used. Patients were categorized as high-risk to develop UGIB if they met ≥1 of the following risk criteria (relevant risk factors): aged ≥65 years (age risk factor); peptic ulcer disease or NSAID gastropathy occurring in the year before their hospital admission (history risk factor); and concomitant use of other NSAIDs, systemic corticoids, oral anticoagulants, or platelet aggregation inhibitors (concomitant medication risk factor). Patients were categorized as candidates to use gastroprotections if they met ≥1 of the relevant risk factors. Patients were categorized as users of gastroprotective treatment if they used proton pump inhibitors, histamine H2-receptor antago nists, or misoprostol at hospital admission. Results: This study comprised 209 cases of NSAID-induced UGIB (129 men, 80 women; mean [SD] age, 71.5 [13.8] years; 128 [61.2%] receiving acetyl sali cylic acid [ASA], with 72 [34.4%] receiving low-dose [80–325 mg] ASA). Preva lence of relevant risk factors for UGIB were as follows: age, 158 (75.6%) patients; history, 37 (17.7%); and concomitant medication, 35 (16.7%). One hundred seventy-eight (85.2%) patients met ≥1 criterion for using a gastroprotective agent; 28 (15.6%) were actually using one. Only the history risk factor was significantly associated with the use of gastroprotective treatment (P = 0.007; odds ratio = 3.17). Conclusions: In this study of NSAID-induced UGIB resulting in hospital admis sion, age was the most common risk factor. However, this criterion was not associated with the use of gastroprotective agents. A large number of cases were associated with the use of ASA, primarily in those receiving low doses. A significant lack of gastroprotective agent use was observed in patients who met the criteria to use them.